Comparative study of wound healing effect of topical Acacia catechu extract and silver sulfadiazine on excisional wound model in guinea pigs - Tangeti, Sunitha; Gabbita, Padmaja; Ponnaluri, Raghunatha R.; Kolasani, Bhanu P. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Impaired and aberrant wound healing imposes a huge financial burden and places an enormous drain in health care resources in the developed world and an insurmountable problem in the developing countries too. In this study, authors have compared the wound healing effect of topical application of Acacia catechu extract with silver sulfadiazine in excisional wound model in guinea pigs. Methods: Twelve guinea pigs were randomly divided into two groups (n=6). The wound healing was observed in excision model. The standard group is treated with silver sulfadiazine (group 1) and the test group with Acacia catechu extract (group 2). The mean wound size expressed in mm2 and the mean percentage of the wound healed was measured on day 0, 4, 8, 12, 16 and 19. Biopsy was done on day 21 for histopathological examination (HPE). Results: Statistical analysis was done by using unpaired t test for between the groups comparison and by using paired t test for within the group comparison. The mean percentage of the wound healed with-in the groups was found to be statistically highly significant (p value <0.001) and in between the groups was found to be statistically non-significant (p value >0.05). A comparable increase in collagen content and granulation tissue was found on HPE in both the groups on day 21. Conclusions: Wound healing effect of the Acacia catechu extract is equal to and comparable with that of silver sulfadiazine.